A new type of (TiZrNbTaHf)N/MoN nanocomposite coating: Microstructure and properties depending on energy of incident ions. (1st August 2018) - Bagdasaryan, A.A.; Pshyk, A.V.; Coy, L.E.; Konarski, P.; Misnik, M.; Ivashchenko, V.I.; Kempiński, M.; Mediukh, N.R.; Pogrebnjak, A.D.; Beresnev, V.M.; Jurga, S.
Abstract: A novel (TiZrNbTaHf)N/MoN nanocomposite coatings, which consist of the nitride of the high-entropy alloy and the binary nitride, were synthesized by vacuum-arc deposition at various substrate biases. The elemental composition, chemical bonding state, phase structure, microstructure and mechanical properties of the coatings were studied by high-resolution experimental methods: SIMS, GDMS, XPS, XRD, HR-TEM and nano-indentation. It was found that the chemical state of the (TiZrNbTaHf)N/MoN coatings has a complex nature, which consist of a mixture of nitrides of constituting elements. It was also shown that the coatings are based on B1 NaCl-structured γ-Mo2 N-phase with a mixture of crystallographic orientations (111), (200), (220) and (311) together with the B1 NaCl-structured (TiZrNbTaHf)N solid-solution phase. First-principles calculations demonstrated that the metal sub-lattice of the (TiZrNbTaHf)N solid solution can be based on Ti1-x Hfy Ta1-x-y, Zr1-x Hfy Ta1-x-y, Zr0.25 Ti0.25 Ta0.5 ternary alloys, which have the lowest mixing energy. The HR-TEM results showed that the nanocomposite nitride coatings have nano-scale multilayer structure with modulation periods ranged from 20 nm to 25 nm. The maximum hardness of approximately 29 GPa demonstrated the coating deposited at a higher energy condition (−200 V) with the thinnest modulation period of bilayer of 20 nm (15 nm of (TiZrNbTaHf)N and 5 nm of Mo2 N). Graphical abstract: